FAKTOR RISIKO KEJADIAN HIPERTENSI PADA REMAJA - Diffa Putra Surya; Annisa Anindita; Celika Fahrudina; Rizki Amalia (Universitas Pahlawan Tuanku Tambusai, 2022)
Sustainable Development Goals (SDGs) are a world agreement for a long period by maximizing resources as the potential of each country and taking into account sustainable development for the well-being of human, environmental, social, and other parts of life in the world. Health is currently the main problem faced by Indonesia, especially the problem of the double burden of disease, where infectious diseases are still the main focus that must be addressed. However, on the other hand, non-communicable diseases (PTM) also show an increasingly positive trend which has an impact on increasing mortality and morbidity rates in Indonesia. The change in epidemiology from infectious diseases to non-communicable diseases is starting to hit developing countries. Hypertension is a cardiovascular disease that is often found in society, including among teenagers. Thus, hypertension is determined to be a major problem and if not treated immediately it will lead to several complications and become a risk factor for the onset of other diseases, such as stroke, diabetes, kidney failure, and heart disease. Based on the results of Riskesdas 2018, there was an increase in the prevalence of 34.1% in the 18-year age group. This literature review uses a systematic method (systematic review). Research also provides an overview of risk factors that are strongly associated with hypertension in adolescents. The results showed that lifestyle became the main factor accompanied by smoking, diet, physical activity, nutritional status, obesity, and education. This is the basis for determining policies in the prevention and control of hypertension.